PRIMA-1 inhibits Y220C p53 amyloid aggregation and synergizes with cisplatin in hepatocellular carcinoma - Paz, Mariana M.; Ferretti, Giulia D. S.; Martins-Dinis, Mafalda M. C.; Ferreira, Beatriz I. S.; Faier-Pereira, Amanda; Barnoud, Thibaut; Moreira, Otacilio C.; Silva, Jerson L.; Cordeiro, Yraima; Rangel, Luciana P. (Frontiers in Molecular Biosciences, 2023)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths worldwide. Although many therapeutic options are available, several factors, including the presence of p53 mutations, impact tumor development and therapeutic resistance. TP53 is the second most frequently mutated gene in HCC, comprising more than 30% of cases. Mutations in p53 result in the formation of amyloid aggregates that promote tumor progression. The use of PRIMA-1, a small molecule capable of restoring p53, is a therapeutic strategy to pharmacologically target the amyloid state mutant p53. Using in silico analysis of p53 mutants, we characterize an HCC mutant p53 cellular model for the study of p53 amyloid aggregation in cells present in HCC cell lines, including 3D-cell culture models. In this study, we demonstrate the unprecedented inhibition of Y220C mutant p53 aggregation by PRIMA-1. In addition, our data show beneficial effects of PRIMA-1 in several “gain of function” properties of mutant-p53 cancer cells, including migration, adhesion, proliferation, and drug resistance. We also discuss the combination of PRIMA-1 and cisplatin as a promising approach for HCC therapy. Taken together, our data support the premise that targeting the amyloid-state of mutant p53 may be an attractive therapeutic approach for HCC, and highlight PRIMA-1 as a new candidate for combination therapy with cisplatin.